Gene-expression profiling discriminates between cerebral malaria (CM) - susceptible mice and CM-resistant mice - Delhaye, N.F.; Coltel, N.; Puthier, D.; Flori, L.; Houlgatte, R.; Iraqi, F.A.; Nguyen, C.; Grau, G.E.; Rihet, P. (Oxford University Press, 2006)
The development of cerebral malaria (CM) in mice with Plasmodium berghei ANKA infection is under genetic control. Brain gene-expression patterns were investigated in well-defined genetically CM-resistant (CM-R; BALB/c and DBA/2) and CM-susceptible (CM-S; C57BL/6 and CBA/J) mice by use of cDNA microarrays. By combining transcriptional profiling with rigorous statistical methods and cluster analysis, we identified a set of 69 genes that perfectly discriminated between mouse strains and between CM-R and CM-S mice. The analysis of gene ontological terms revealed that the genes that clustered and were related to susceptibility to CM preferentially belonged to some biological process classes, such as those pertaining to immune responses. Using a false discovery rate of 5% and the Welch t test, we identified 31 genes with consistent differential expression between CM-R and CM-S mice. These data indicate that microarray analysis may be useful for identification of candidate genes that are potentially responsible for resistance or susceptibility to mouse CM and suggest that candidate genes identified in mice could be specifically tested in humans for an association with disease severity.